Hadith #3576 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Rja'a al-Ansari رجاء الأنصاري; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
“If any do fail to judge (by the light of) what Allah has revealed, they are (no better than) unbelievers” up to “wrongdoers.” These three verses were revealed about the Jews, particularly about Quraizah and al-Nadir.
Grade: Hasan